2016
DOI: 10.3892/etm.2016.3309
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell-derived factor-1 promotes human adipose tissue-derived stem cell survival and chronic wound healing

Abstract: Adipose tissue-derived stem cells (ADSCs) hold great potential for the stem cell-based therapy of cutaneous wound healing. Stromal cell-derived factor-1 (SDF-1) activates CXC chemokine receptor (CXCR)4+ and CXCR7+ cells and plays an important role in wound healing. Increasing evidence suggests a critical role for SDF-1 in cell apoptosis and the survival of mesenchymal stem cells. However, the function of SDF-1 in the apoptosis and wound healing ability of ADSCs is not well understood. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…S6 ). This is in good agreement with the previous reports that cell sheets are quite effective for the chronic wound healing 44 46 .…”
Section: Resultssupporting
confidence: 93%
“…S6 ). This is in good agreement with the previous reports that cell sheets are quite effective for the chronic wound healing 44 46 .…”
Section: Resultssupporting
confidence: 93%
“…The anti-inflammatory and angiogenic capacity, the ability to release a range of growth factors (especially vascular and fibroblast related), and the regulatory role in MMPs secretion makes MSCs ideal candidates for the treatment of AD. Recent studies have highlighted the critical importance of MSCs as essential constituents for the aortic aneurysm or dissection niche through inducing chemokine and cytokine secretion ( 31 ) and wound healing ( 32 , 33 ). More and more studies are providing insights into aberrant microenvironment of AD pathology, and MSCs have been recognized as a crucial element for AD microenvironment ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs participate in various steps of the wound healing process, including the enhancement of epidermal cell growth, angiogenesis, collagen deposition, anti‐inflammation, and wound closure . However, previous studies have shown that the therapeutic effect of MSCs is limited due to their poor survival after transplantation . Indeed, previous study showed that the survival rate of MSCs at 24 hours post‐transplantation is relative low, and ROS make a great contribution of this low survival rate .…”
Section: Discussionmentioning
confidence: 99%